Medicinal Plants and Natural Product Research - Stankovic, Milan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book entitled Medicinal Plants and Natural Product Research describes various aspects of ethnopharmacological uses of medicinal plants; extraction, isolation, and identification of bioactive compounds from medicinal plants; various aspects of biological activity such as antioxidant, antimicrobial, anticancer, immunomodulatory activity, etc., as well as characterization of plant secondary metabolites as active substances from medicinal plants.